If It's Smart, It's Vulnerable - Hypponen, Mikko (John Wiley & Sons, Incorporated, 2022)
Reimagine the future of the internet All our devices and gadgets-from our refrigerators to our home security systems, vacuum cleaners, and stereos-are going online, just like our computers did. But once we've successfully connected our devices to the internet, do we have any hope of keeping them, and ourselves, safe from the dangers that lurk beneath the digital waters? In If It's Smart, It's Vulnerable, veteran cybersecurity professional Mikko Hypponen delivers an eye-opening exploration of the best-and worst-things the internet has given us. From instant connectivity between any two points on the globe to organized ransomware gangs, the net truly has been a mixed blessing. In this book, the author explores the transformative potential of the future of the internet, as well as those things that threaten its continued existence: government surveillance, censorship, organized crime, and more. Readers will also find: Insightful discussions of how law enforcement and intelligence agencies operate on the internet Fulsome treatments of how money became data and the impact of the widespread use of mobile supercomputing technology Explorations of how the internet has changed the world, for better and for worse Engaging stories from Mikko's 30-year career in infosecPerfect for anyone seeking a thought-provoking presentation of some of the most pressing issues in cybersecurity and technology, If It's Smart, It's Vulnerable will also earn a place in the libraries of anyone interested in the future of the internet.